Pengaruh Kualitas Produk dan Promosi terhadap Keputusan Pembelian Susu UHT Ultramilk dikalangan Gen Z Kabupaten Bekasi: The Influence of Product Quality and Promotion on Gen Z's Decision to Purchase Ultramilk UHT Milk in Bekasi Regency - Ari Zahari; Eulin Karlina (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Generation Z is a group of young consumers with dynamic consumption patterns and high responsiveness to product quality and promotional activities. This study aims to analyze the influence of product quality and promotion on the purchase decision of UHT Ultramilk among Generation Z in Bekasi Regency. The research uses a quantitative method with data collected through questionnaires. The population consists of Generation Z individuals (ages 13–28) residing in Bekasi. A sample of 97 respondents was determined using the Slovin formula and selected randomly. Data analysis includes validity and reliability tests, t-test, F-test, coefficient of determination (R²), and multiple linear regression analysis. The t-test results show that product quality (X1) has a significant effect on purchase decision (Y), with a t-value of 4.918 > t-table 1.661. Promotion (X2) also has a significant effect, with a t-value of 3.988 > t-table. The F-test shows a simultaneous influence of X1 and X2 on Y, with an F-value of 13.531 > F-table 3.093. In conclusion, both product quality and promotion have a positive and significant influence—both partially and simultaneously—on the purchase decision of UHT Ultramilk among Generation Z in Bekasi Regency